2017
DOI: 10.1016/j.ijdevneu.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of Glial fibrillary acidic protein in Chinese children with autism spectrum disorders

Abstract: The data indicates that serum GFAP levels may be associated with severity of ASD among Chinese children, suggesting the hypothesis that increased serum levels of GFAP could be implicated in the pathophysiology of autism in Chinese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
9
2
Order By: Relevance
“…However, the small study groups with only four children diagnosed with autism do not allow any conclusion to be drawn. These results differ from previous studies, in which elevated levels of GFAP were found in CSF [11] and serum [12] in children with autism compared to controls. However, none of the children with autism and PANS in our study had intellectual disability, while this was present in 70% of the children with autism reported in the 1990s [11].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the small study groups with only four children diagnosed with autism do not allow any conclusion to be drawn. These results differ from previous studies, in which elevated levels of GFAP were found in CSF [11] and serum [12] in children with autism compared to controls. However, none of the children with autism and PANS in our study had intellectual disability, while this was present in 70% of the children with autism reported in the 1990s [11].…”
Section: Discussioncontrasting
confidence: 99%
“…In one aetiological subgroup of children with autism, consisting of three children with a basal ganglia disorder, the highest GFAP levels were found [11]. Also a more recent study, using serum levels of GFAP, demonstrated elevated levels in children with autism compared to controls [12].…”
Section: Introductionmentioning
confidence: 86%
“…In our study serum GFAP levels were significantly increased in ASD patients, with a positive correlation found with CARS score showing severity of autism in all subjects. Wang et al also found increased levels of GFAP in the serum of autistic children (Wang et al, 2017). The GFAP findings in this study are in accordance with a previous postmortem study which found increased GFAP levels in the brain (Laurence and Fatemi, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…The clinical heterogeneity in ASD children has encouraged increasing interest in biomarkers as potentially useful indicators for diagnosis and treatment. Recently, a number of studies have attempted to identify potential blood-based biomarkers based on neurophysiological and biochemical alterations, for example, brain-derived neurotrophic factor (BDNF) [ 39 41 ], neurotrophin-4 (NT-4) [ 41 ], serotonin (5-HT) [ 42 , 43 ], neopterin [ 44 ], and the glial fibrillary acidic protein [ 45 ]. However, no biomarkers to date have shown high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%